2004
DOI: 10.1063/1.1834994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the satellite lines and opacity on the extreme ultraviolet emission from high-density Xe plasmas

Abstract: Extreme ultraviolet (EUV) emission from Xe plasma in the λ=13.5nm band is theoretically investigated for lithographic application. It appears that a large number of satellite lines due to the 4d–4f, 4d–5p, and 4p–4d transitions significantly contribute to the emission over the spectral range from 10to17nm. At electron densities above 1020∕cm3, laser-produced Xe plasmas attain quasilocal thermodynamic equilibrium (LTE) in order to make the emission intensity in the 13.5nm band comparable to that in the 11nm ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…These spectra contain resonant UTA lines around 6.7 nm and many satellite emission lines at wavelengths longer than 6.7 nm in sufficiently dense plasmas. The spectral behavior is similar to that of Nd:YAG laser-produced xenon (Xe) plasmas, with resonant lines around 11 nm and satellite emission at wavelengths longer than 11 nm, especially around 13.5 nm [19,20]. Figure 2(a) shows the laser intensity dependence on the EUV CE when the laser wavelength of 1064 nm is irradiated according to maximizing 6 the EUV emission in Fig.…”
mentioning
confidence: 69%
“…These spectra contain resonant UTA lines around 6.7 nm and many satellite emission lines at wavelengths longer than 6.7 nm in sufficiently dense plasmas. The spectral behavior is similar to that of Nd:YAG laser-produced xenon (Xe) plasmas, with resonant lines around 11 nm and satellite emission at wavelengths longer than 11 nm, especially around 13.5 nm [19,20]. Figure 2(a) shows the laser intensity dependence on the EUV CE when the laser wavelength of 1064 nm is irradiated according to maximizing 6 the EUV emission in Fig.…”
mentioning
confidence: 69%
“…12c (in this case the shape is more ellipsoidal). As the mass and electron density is constant in the sphere (not in time but in space), we show that the speed inside the sphere remains homothetic and consequently all the formulas for the kinetic energy, radiative losses [53] of energy, and impulsion balance [56] remain very simple.…”
Section: Comparison Of Experimental Data Of Xe Laser-produced Plasma mentioning
confidence: 98%
“…The interaction of configurations sharpens the 4d-(4f/4p) group of resonant lines. It has been shown that the interaction of configurations has a strong influence on satellite lines and reduces the width of the main 4d-4f/4p-4d broad satellite structure [42,51,53]. Therefore, interaction of all configurations has systematically been included in our HULLAC calculations leading to energy matrices including more than 3000 levels.…”
Section: Comparison Of Experimental Data Of Xe Laser-produced Plasma mentioning
confidence: 99%
“…The dip indicates that the expanding plasma strongly absorbs the 13.5 nm light emitted from the inside layer. The broad spectrum that is clearly observed in the EUV spectrum from the 20 -30 nm-depth layer can be attributed to the satellite lines emitted from the multiply excited Sn ions and the opacity broadening during the radiation transport [17]. EUV emission was not observed from the layer located initially deeper than 30 nm, because Sn atoms in this layer were not sufficiently ionized to emit any EUV radiation.…”
mentioning
confidence: 91%